THE EFFECT OF ENDORPHIN MASSAGE TO REDUCING PAIN INTENSITY AND INCREASING COMFORT IN THE FIRST STAGE OF LABOR IN PMB JAWIRYAH, S.ST - Gadis Halizasia; Ferdi Riansyah; Nelva Riza; Ulfa Mahirah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Childbirth is a physiological process that will be experienced by every pregnant woman in her reproductive cycle. Changes that occur in the body to prepare for childbirth often cause pain in the mother. Labor pain often affects the physical and psychological condition of the mother, such as causing anxiety, fatigue, and reducing comfort, which can ultimately slow down the labor process (Fauzani, et al 2024). Ways to relieve labor pain can be done pharmacologically and non-pharmacologically. One non-pharmacological method to reduce pain during labor is endorphin massage. This study aims to determine the effect of endorphin massage on reducing pain intensity and increasing comfort in the first stage of labor. The research method used is a quasi-experimental design using a pre and post-test without control design. In this design, researchers only intervene in one group without a comparison. The sampling technique in this research was a total sampling technique with a sample of 40 respondents. the results of the Wilcoxon signed rank test before being given the distraction technique and after being given the distraction technique that the calculated Z is -5.477b and significant at 0.000. this shows that the significant value of 0.000 is smaller than 0.05 (5% error rate). So it can be concluded that there is a decrease in the level of normal labor pain in mothers from the results before being given Endorphine Message and after Endorphine Message. to overcome or teach ways to reduce pain in normal labor so that it can maintain excellence, so that joint services improve.